Structural insights into HIV-1 protease flap opening processes and key intermediates. Issue 71 (21st September 2017) - Yu, Yuqi; Wang, Jinan; Chen, Zhaoqiang; Wang, Guimin; Shao, Qiang; Shi, Jiye; Zhu, Weiliang
Abstract : The study provided an integrated view of the transition pathway of the flap opening of HIV-1 protease using MD simulation. Abstract : HIV-1 protease (PR) is an effective drug target for antiviral inhibitors. The conformational dynamics in the flaps of HIV-1 PR plays a crucial role in the mechanism of substrate binding. Here, the structural properties of the functionally important intermediate states of the flap opening transition of HIV-1 PR have been characterized by enhanced sampling molecular dynamics simulation as well as long-time conventional non-enhanced simulations at atomic level. Not only crystallographically measured "closed" and "semi-open" structures but also a novel "curled" structure of HIV-1 PR is captured by both kinds of simulations qualitatively and quantitatively. The observation of the "curled" intermediate state helps to connect all other functionally important states to provide an integrated view of the transition pathway of the flap opening of HIV-1 PR (closed → curled → semi-open → fully open). The key residue–residue interactions which are broken or formed in the transition are analyzed to reveal the inherent driving force for the protein conformational transition.